Passengers’ Perspective Toward Airport Service Quality (ASQ) (Case Study at Soekarno-Hatta International Airport) - Ridha Kurniawan; Samuel Petros Sebhatu; Sara Davoudi (Journal of the Civil Engineering Forum, 2017)
Passenger satisfaction towards airport service quality is influenced by the level of service at the previous service quality. It causes the new facility is expected to exceed the previous service quality. Service quality improvement of people mover system in Grand Design of Soekarno Hatta International Airport (SHIA) expected to support increasing airport service quality management. People mover existing conditions that occur on a free shuttle bus has caused some customer complaint. The purpose of this thesis is providing strategic support as complaint handling on people mover system to enhancing SHIA service quality. The discussion involves a passenger's perspectives, passengers’ satisfaction, and airport service quality to get a purpose of research. This thesis utilizes Fodness and Murray theory regarding the accurate scale to measure SHIA service quality by using Servqual method and Kano Model approach. Airport Service Quality (ASQ) aims to give an airport more competitive in the relationship between business and operations. In this thesis offers support strategy in service quality attributes and considerations to assist airport management in improving airport service quality. This thesis finds the value gap between airport management and passengers’ perspectives that serve as accurate scale in each service attributes on people mover facility at SHIA that must be met to achieve satisfaction based on passengers’ perspectives. Also, this thesis finds several services attributes that must be met on people mover facility at SHIA as a basic service needs by passengers need. Airport management at SHIA should focus on the improved operating system of people mover system related to attributes punctuality, free of charge, information about the schedule, headway, and safety. This thesis presents the relationship between the value gap with service attributes that must be met by passengers’ perspectives, passengers’ satisfaction, and airport service quality. This thesis shows how an airport service quality is decided based on gap scale between airport management with passenger perspectives and priority services as passengers’ guarantee.